Redox agent enhanced chemical mechanical polishing of thin film diamond. (April 2018) - Mandal, Soumen; Thomas, Evan L.H.; Gines, Laia; Morgan, David; Green, Joshua; Brousseau, Emmanuel B.; Williams, Oliver A.
Abstract: The chemical nature of the chemical mechanical polishing of diamond has been examined by adding various redox agents to an alkaline SF1 polishing slurry. Three oxidizing agents, namely hydrogen peroxide, potassium permanganate and ferric nitrate, and two reducing agents, oxalic acid and sodium thiosulfate, were added to the SF1 slurry. Oxalic acid produced the fastest polishing rate while hydrogen peroxide had very little effect on polishing, probably due to its volatile nature. X-ray photoelectron spectroscopy (XPS) reveals little difference in the surface oxygen content on thesamples polished using various slurries. This suggests that the addition of redox agents do not increase the density of oxygen containing species on the surface but accelerate the process of attachment and removal of Si or O atoms within the slurry particles to the diamond surface. Graphical abstract: